2003
DOI: 10.1111/1467-9620.00274
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Mind: The Matrix, Metaphors, and Re-imagining Education

Abstract: Free your mind." This exhortation becomes a refrain in the Wachowski brothers' film, The Matrix (Silver, 1999), a visual study of movements of mind. Set sometime around the year 2199, the movie follows Morpheus, the leader of an underground resistance movement, as he guides the young hero, Neo, to a startling recognition: that what he believes to be reality at the end of the 20 th century is in fact a computer-generated dream-world called the Matrix. This "prison for [the] mind," as Morpheus describes it, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 47 publications
3
40
0
6
Order By: Relevance
“…We agree with Hardcastle, Yamamoto, Parkay & Chan (1985), and Cook-Sather (2003) that metaphors are the larger constructs under which people organize their thinking and from which they plan their actions on the multiple environments in which they participate including, to some extent, how they teach and work with students.…”
Section: Metaphorssupporting
confidence: 52%
See 1 more Smart Citation
“…We agree with Hardcastle, Yamamoto, Parkay & Chan (1985), and Cook-Sather (2003) that metaphors are the larger constructs under which people organize their thinking and from which they plan their actions on the multiple environments in which they participate including, to some extent, how they teach and work with students.…”
Section: Metaphorssupporting
confidence: 52%
“…In our data we found that the teaching context contributed to the reaffirmation of beliefs with only some slight changes in basic conceptualizations of teaching and children over the two years of study three. These beliefs and conceptual metaphors of both Svetlana and Juan stand in stark contrast to the findings of Cook-Sather (2003). It is her conclusion that the two metaphors that historically and currently still dominate U.S. schooling are (a) education as production with the school as a factory and (b) education as remedy with students as diseased individuals in need of a cure.…”
Section: Case Study I: Svetlanamentioning
confidence: 88%
“…Likewise, de Guerrero and Villamil (2002) elicited and reported metaphors from 22 Puerto Rican teachers about teachers' and learners' roles and called attention to the merits of such information in the professional development of language teachers and the enhancement of their practice. Cook-Sather (2003) posited that two metaphors dominated the formal educational system in the United States, that is, "education as production" and "education as cure." In the field of foreign language teaching, Herron (1982) identified two basic metaphors driving curriculum theories in foreign language education: "the mind-body metaphor," in which language learning is viewed as mental gymnastics aimed to strengthen and discipline the learner's mind and "the production metaphor," where the aim of language learning was to produce a marketable and skillful workforce.…”
Section: Metaphor Studies In Language Teaching and Learningmentioning
confidence: 99%
“…Teachers who conceptualise classroom communication according to the ShannonWeaver model -as a process of sending and receiving information -are prone to view the teaching process mostly as a process of transmitting knowledge to the students. Metaphors, present at all levels of the educational discourse (Block, 1992;Ben-Peretz, Mendelson & Kron, 2003;Chen, 2003) can help teachers to articulate and construct their professional experiences (Kramsh, 2003;Nikitina & Furuoka, 2008) and guide their teaching practice (Cortazzi & Jin, 1999;Tăușan, 2011;Cook-Sather, 2003;Badley & Van Brummelen, 2012 …”
Section: Introductionmentioning
confidence: 99%